Effect of exogenous fibrolytic enzymes supplementation on nutrient intake and digestibility in Black Bengal kids - CHATTERJEE, A; KUMAR, MANOJ; DUTTA, T K; MOHAMMAD, A; BHAKAT, C; RAI, SAROJ; MANDAL, D K; KARUNAKARAN, M (The Indian Journal of Animal Sciences, 2023)
The present study was carried out to evaluate the effect of supplementation of exogenous fibrolytic enzymes (EFE) to the Total Mixed Ration (TMR) at two different levels on intake, nutrient digestibility and nutrient availability in Black Bengal kids. A digestibility trial was conducted on 15 post-weaned Black Bengal kids divided into three groups. Control (T0) group was fed ad lib. TMR was prepared from concentrate mixture and green fodder @ 40: 60 on DM basis. T1 and T2 groups were supplemented with EFE cellulase and xylanase @ 8000 and 16000 IU/kg TMR DM and 12000 and 24000 IU/kg TMR DM, respectively. The study revealed significantly higher digestibility of nutrients, i.e. DM, OM, EE, NDF, ADF, hemicellulose, cellulose and total carbohydrates in both enzyme supplemented groups than the control group. However, the digestibility of CP, cellulose and hemicellulose was significantly higher only in T2 group than the control. There was no significant difference between two enzyme supplemented groups in terms of digestibility of different nutrients except for CP which was significantly higher in T2 than T1. The difference in voluntary intake of DM and OM were non-significant but the intake of CP, DCP and TDN were higher in enzyme supplemented groups. Similarly, TDN, DE and ME content of the diet were also higher in two enzyme supplemented groups than control. However, there was no significant difference between T1 and T2 in terms of nutrient availability and intake. Based on the present study, supplementation of EFE @ cellulase 8000 and xylanase 16000 IU/ kg DMwas found to be optimum for improving the nutrient digestibility and availability in Black Bengal kids, which may further improve the productive and reproductive performance of the animals.